Knowledge Transfer From Business Schools to Firms Through Academics: An AMO Perspective in an Emerging Economy - Christopher Boafo; Utz Dornberger (Thunderbird International Business Review, 2024)
Society's growing demand for knowledge transfer from higher education institutions to firms through academics is a notable trend. Nonetheless, the nuances of how business school academics perceive their engagement in knowledge transfer to firms remain inadequately explored. This research endeavors to bridge this knowledge gap by drawing upon interviews conducted with 52 business school academics in Ghana. The synthesized findings derived from the interpretive phenomenological data analysis provide crucial insights grounded in the ability–motivation–opportunity theory framework. Within this framework, "opportunity" describes image- and project-opportunity context drivers, such as media engagement, goodwill, in-service training students, and projects by international development organizations fostered through relationship-building and networking. "Motivation" explains the established national, societal, and self-serving mandates, stimulating institutional-, society-, and person-driven motivations. "Ability" encompasses the capacity of academics to employ both generic and relational mechanisms. The interplay among ability, motivation, and opportunity catalyzes the creation of various knowledge content types linked to specific market contexts.
Keywords: 330; ability–motivation–opportunity theory; academic engagement; business school; internationalization; sub-Saharan Africa; university–business collaboration